Detection of Connectivity Disruption in Wsn using Edcd Method (International Journal of Advanced Research in Computer Science, 2017)
Wireless sensor Networks (WSNs) typically suffer from noncontiguous property caused by its varied aspects like restricted battery power of a node and unattended operation vulnerable to hostile meddling. This property ends up in unknown route selection, waste of resources and loss of knowledge. Wireless Sensor network will get splitted into multiple connected parts in line for the crash of a number of its nodes that is referred as a â€œcutâ€. Complications like unfit for dynamic network re-arrangement, Single path routing technique occur in existing state of affairs. In this paper, EDCD method is proposed as the solution for cut detection problem in destination-node, in which cuts are identified based on a given set of destinations. Here cut detection procedures are introduced for WSN applications and then expand the number of target destinations and proposed the Enhanced Distributed Cut Detection.Â Keywords- Wireless Sensor networks, cut detection, EDCD, DSSD, MINCUT, internet protocol